A CASE OF VERTEX POSTURE CAUSING OYSTOCIA IN A BHARAT MERINO EWE - DAS, G K (The Indian Journal of Animal Reproduction, 2023)
A case of vertex posture (butt presentation) with bilateral shoulder flexion causing dystocia in aBharat Merino ewe reared under sub-temperate climate of India is recorded.
Keywords: Ewe; Dystocia; Vertex posture; Butt presentation; Postural defects